Blood Profile of Beef Cattle offered Mulberry Leave Meal to Substitute Feed Concentrate - S. Syahrir; K. G. Wiryawan; A. Parakkasi; M. Winugroho (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2010)
The purpose of this experiment was to examine the effects of mulberry leave meal to substitute concentrate in rice straw based ration on blood profiles of Ongole crossbreed cattle. This experiment was carried out according to completely randomized design consisted of 3 treatments and 4 replications. The treatments were P1 (50% rice straw + 50% concentrate), P2 (50% rice straw + 25% concentrate + 25% mulberry leave meal), and P3 (50% rice straw + 50% mulberry leave meal). Parameters measured were blood profiles, i.e. blood glucose, blood cholesterol and blood HDL. The results showed that substitution of concentrate with mulberry leave meal significantly reduced (P<0.05) blood glucose and increased blood cholesterol and HDL. It is concluded that mulberry leave meal can be used to substitute concentrate and give a positive effect on glucose, cholesterol,and HDL contents of blood.